Distribution of dissolved and particulate Fe in an estuarine system at Bagan Pasir, Perak - Muhamad Kamel, Syaza Syafiqah; Mohamed @ Mohd Ramli, Khairul Nizam; Mohamat Yusuff, Ferdius @ Ferdaus; Amiruddin, Abd Muhaimin (Universiti Putra Malaysia Press, 2019)
The distribution of dissolved iron (dFe) and particulate iron in the estuarine system was studied where in-situ water sampling stations were selected at Bagan Pasir, Perak. The concentration of dFe was 1.17±0.28 mg/L on average at the estuary, while in freshwater samples its concentration was 0.08±0.00 mg/L. This study found that the concentration of particulate Fe in freshwater system was higher than that in the estuary system. The Fe concentration was 0.95±0.03 mg/kg and 0.80±0.18 mg/kg at the freshwater and estuary systems, respectively. We have applied a distribution coefficient (KD) in order to quantify the partitioning of Fe between the particulate (>0.45 µm) and dissolved (<0.45 µm) phases. The KD value of Fe in the freshwater system was much higher compared to that in the estuary, where the KD value was 12.18 in freshwater and 0.48 -1.31 in the estuary. This indicated that Fe in this area has a strong affinity with the particulate phase in a freshwater system and this is probably due to the anthropogenic input. On the other hand, Fe may exist in colloidal or organic ligands which probably originate from surface sediment or a biological process in water columns at the estuarine area.